Comparative analysis of integrative and conjugative mobile genetic elements in the genus mesorhizobium - Colombi, Elena; Perry, B.J.; Sullivan, J.T.; Bekuma, A.A.; Terpolilli, J.J.; Ronson, C.W.; Ramsay, Josh (MICROBIOLOGY SOC, 2021)
Members of the Mesorhizobium genus are soil bacteria that often form nitrogen-fixing symbioses with legumes. Most char-acterised Mesorhizobium spp. genomes are ~8 Mb in size and harbour extensive pangenomes including large integrative and conjugative elements (ICEs) carrying genes required for symbiosis (ICESyms). Here, we document and compare the conjugative mobilome of 41 complete Mesorhizobium genomes. We delineated 56 ICEs and 24 integrative and mobilizable elements (IMEs) collectively occupying 16 distinct integration sites, along with 24 plasmids. We also demonstrated horizontal transfer of the largest (853,775 bp) documented ICE, the tripartite ICEMspSymAA22. The conjugation systems of all identified ICEs and several plasmids were related to those of the paradigm ICESym ICEMlSymR7A, with each carrying conserved genes for conjugative pilus formation (trb), excision (rdfS), DNA transfer (rlxS) and regulation (fseA). ICESyms have likely evolved from a common ancestor, despite occupying a variety of distinct integration sites and specifying symbiosis with diverse legumes. We found extensive evidence for recombination between ICEs and particularly ICESyms, which all uniquely lack the conjugation entry-exclusion factor gene trbK. Frequent duplication, replacement and pseudogenization of genes for quorum-sensing-mediated activation and antiactivation of ICE transfer suggests ICE transfer regulation is constantly evolving. Pangenome-wide association analysis of the ICE identified genes potentially involved in symbiosis, rhizosphere colonisation and/or adaptation to distinct legume hosts. In summary, the Mesorhizobium genus has accumulated a large and dynamic pangenome that evolves through ongoing horizontal gene transfer of large conjugative elements related to ICEMlSymR7A.